Atypical Human Effector/Memory CD4+ T Cells With a Naive-Like Phenotype - Caccamo, Nadia; Joosten, Simone A.; Ottenhoff, Tom H. M.; Dieli, Francesco (Frontiers in Immunology, 2018)
The induction of adaptive immunological memory, mediated by T and B cells, plays an important role in protective immunity to pathogens induced by previous infections or vaccination. Naive CD4+ T cells that have been primed by antigen develop into memory or effector cells, which may be distinguished by their capability to exert a long-term and rapid response upon re-challenge by antigen, to produce distinct cytokines and surface marker expression phenotypes such as CD45RA/RO, CD27, CD62L and CCR7. Recent evidence, however, has highlighted that CD4+ naive T cells are much more heterogeneous that previously thought, and that they harbour diversity in phenotypes, differentiation stages, persistence, functions and anatomic localizations. These cells represent cellular subsets that are extremely heterogeneous and multifunctional at their very initial stages of differentiation, with the potential to become “atypical” memory and effector cells. In this mini review, we focus on recently obtained data from studies in humans, in which this newly recognized heterogeneity in the naive T cell pool was discovered in terms of surface marker expression, cytokine production or transcriptomic profiles. The deep analysis of immune functions at the single cell level combined with a better understanding of the generation and maintenance of the various atypical memory CD4+ T cell subsets with a naive-like phenotype will be important in immune-monitoring of vaccination and immunotherapies in infectious diseases.